THERMAL REQUIREMENTS OF Ceraeochrysa cubana (Neuroptera: Chrysopidae) EMBRYONIC PERIOD SUBMITTED TO ARTIFICIAL DIETS AT ADULT STAGE - Nunes, Gilmar da Silva [UNESP]; Souza, Mileny dos Santos de; Vitoriano Dantas, Thais Aparecida; Nascimento, Izabela Nunes do; Oliveira, Gemerson Machado de; Oliveira, Roberio de; Batista, Jacinto de Luna (Univ Federal Uberlandia, 2018)
Green lacewings can be mass reared to market their eggs. The ideal temperature is a main factor for egg storage or scheduling of insect production. This study aimed to evaluate the influence of Ceraeochrysa cubana adult feeding on incubation period and feasibility off eggs storage under different temperatures. Adults were submitted to four artificial diets: honey + brewer's yeast (standard diet), molasses + brewer's yeast, honey + bee pollen and molasses + bee pollen. Incubation period was recorded keeping eggs at six different temperatures: 21, 23, 25, 27, 29 and 31 degrees C. requirements. We determined the duration of the incubation period and egg feasibility of C. cubana. In addition, we estimated the base temperature (Tb) and thermal threshold (K) for the green lacewing incubation. Regardless of diet, incubation period decreases according to increased temperature, which is indicated between 21 and 29 degrees C for better development and egg feasibility. Adult feeding influences thermal constant, however, does not influence base temperature of the eggs, which varies from 15 to 18 degrees C. Our results can serve as a basis for the choice of adults' diet and temperature for the storage of eggs during the mass rearing of C. cubana.
Keywords: Egg storage; Green lacewings; Mass rearing; Temperature